A Comparison of The Effectiveness of The Tera Gymnastics Breathing Technique with Deep Breathing Techniques on Reducing Labor Pain - Ryka Juaeriah; Yuliana; Gemilang Rahma Annisa (Jurnal Kesehatan Budi Luhur: Jurnal Ilmu-Ilmu Kesehatan Masyarakat, Keperawatan, dan Kebidanan, 2025)
The most common problem that arises in maternity mothers is labor pain. Pain during labor accompanied by fear will slow down the labor process. Labor pain will cause hyperventilation, increase oxygen consumption, cause respiratory alkalosis, vasoconstriction of blood vessels in the uterus and acidosis in the fetus. Increasing noradrenaline will lower blood to the placenta and decrease uterine contractions, thereby interfering with the safety of the mother and fetus and the success of vaginal partus. Tera gymnastics can stimulate the heart's ability to pump blood to meet oxygen needs so that the heart works with relaxation, resting pulse, and blood pressure becomes stable. The purpose of this study was to determine the comparison of the effectiveness of deep breathing and tera gymnastics breathing techniques on pain reduction during the first childbirth. This study uses a quasi-experimental design with two groups pretest-posttest design. The research was carried out at TPMB "P" Cimahi City which was carried out in February – September 2024. The sample in this study is maternity mothers during the active phase 1 who meet the inclusion and exclusion criteria. The sampling technique used was non-random sampling by purposive sampling totaling 40 mothers. The sample in this study was divided into 2 groups, namely the intervention group and the comparison group. Data analysis using the Mann-Whitney test. Based on the findings from the pain scale measurements, the tera gymnastics breathing technique demonstrated a greater reduction in pain with a delta value of 4.4, compared to 2.8 in the deep breathing technique. This indicates that tera gymnastics breathing is more effective in alleviating pain among laboring women during the active phase of the first stage of labor. It is recommended that expectant mothers and healthcare providers implement tera gymnastics and deep breathing techniques during labor to help ease pain and enhance maternal comfort.